The Middle East journal (Washington, D.C Middle East Institute, 1949)
The Middle East Journal is the oldest peer-reviewed publication dedicated solely to the study of the Middle East. First printed in 1947, the Journal continues to present readers with original and objective research and analysis, as well as source material, on the area from Morocco to Pakistan and including Central Asia. The Journal provides the background necessary for an understanding and appreciation of the region’s political and economic development, cultural heritage, and ethnic and religious diversity.
Full text articles availble on JSTOR: https://www.jstor.org/journal/middeastj
Keywords: Economic development; ECONOMIC DEVELOPMENT; POLITICAL DEVELOPMENT; CULTURAL HERITAGE; MIDDLE EAST; RESEARCH; PERIODICALS